Interior Design Of The Baba-Nyonya Eclectic Shophouses In Melaka - Chung , Siaw Ting (2012)
The Straits Chinese, fondly known as the Baba-Nyonya or China Peranakan. The Baba-Nyonya culture features a hint of the people’s cultures of the Malay (Javanese, Batak), Thai and European (Dutch, Portuguese and British) cultures but mainly revolves around Malay and Chinese cultures. Nonetheless, the supreme architectural achievement of this minority group- their eclectic shophouses is now facing a crisis which may determine its survival. The problem is critical for there is inconsistently lack of sound knowledge in conservation of their shophouses.